Dynamic seismic signatures of saturated porous rocks containing two orthogonal sets of fractures: Theory versus numerical simulations - Guo, Junxin; Rubino, Jorge German; Glubokovskikh, Stanislav; Gurevich, Boris (Oxford University Press, 2018)
Fil: Guo, Junxin. Curtin University; Australia